2022
DOI: 10.3389/fonc.2022.881801
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 Acts as an Onco-immunological Biomarker With Value in Assessing the Tumor Microenvironment, Pathological Staging, Histological Subtypes, Therapeutic Effect, and Prognoses of Several Types of Cancer

Abstract: The suppressor of cytokine signaling (SOCS) family contains eight members, including SOCS1–7 and CIS, and SOCS3 has been shown to inhibit cytokine signal transduction in various signaling pathways. Although several studies have currently shown the correlations between SOCS3 and several types of cancer, no pan-cancer analysis is available to date. We used various computational tools to explore the expression and pathogenic roles of SOCS3 in several types of cancer, assessing its potential role in the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…The current study found that GBM with high SOCS1/2/3/4 expression had a poor prognosis. Our group previously found a potential correlation between SOCS3 expression and GBM 45 . The current study verified the presence of high SOCS3 expression in a variety of cell lines through cell experiments, and the RT‐qPCR and IHC analyses of human tissue specimens demonstrated the high expression of SOCS3 in GBM.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current study found that GBM with high SOCS1/2/3/4 expression had a poor prognosis. Our group previously found a potential correlation between SOCS3 expression and GBM 45 . The current study verified the presence of high SOCS3 expression in a variety of cell lines through cell experiments, and the RT‐qPCR and IHC analyses of human tissue specimens demonstrated the high expression of SOCS3 in GBM.…”
Section: Discussionsupporting
confidence: 83%
“…Our group previously found a potential correlation between SOCS3 expression and GBM. 45 The current study verified the presence of high SOCS3 expression in a variety of cell lines through cell experiments, and the RT-qPCR and IHC analyses of human tissue specimens demonstrated the high expression of SOCS3 in GBM. To further explore the potential role of SOCS3 as a marker for poor prognosis of GBM, SOCS3 was knocked down by siRNA, and it was found that cell lines with reduced SOCS3 expression had lower proliferation levels, and reduced migration and invasion abilities.…”
Section: Discussionsupporting
confidence: 71%
“…39 In the current investigation, the disparity between proliferation and apoptosis was illustrated by raising the level of SOCS3 and diminishing the level of PPAR-γ and the proapoptotic caspase-3 in HepG2 group (Figure 5). As reported in the study of Dai et al, 40 SOCS3 is an immune-oncogenic molecule that is predominantly implicated in the genesis of tumor mainly via the JAK/STAT signaling transduction pathway and cytokine receptor activation. These findings suggest that SOCS3 is important for the genesis and progression of several malignancies and may serve as an important objective for cancer detection and treatment.…”
Section: Discussionmentioning
confidence: 89%
“…For example, Dai et al showed that SOCS3 was useful for the diagnosis, staging, histological subtyping, prognosis, and therapeutic response in several types of cancer in the context of immuno-oncology via multiple mechanisms, and that genetic or epigenetic alterations in SOCS3 frequently predict a poor prognosis. SOCS3 expression and changes in the tumor-cell immune infiltration were predicted through the presence of immunosuppressive cells (MDSCs, CAFs, M2-TAMS, and Tregs) that promote T-cell exclusion [ 65 ]. Therefore, frequent follow-up of more patients co-expressing PDL-1 and SOCS3 could provide future insights.…”
Section: Discussionmentioning
confidence: 99%